Earthquake Disaster Mitigation Strategy: Lessons Learned from Indonesia - Yuliyanti, Mela; Natalia, Reva Klaura; Pradani, Citra Putri; Anggraeni, Dini; Astuti, Septin Puji; Setyaningrum, Ika Feni (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
Purpose: Determining the mitigation strategy for earthquake-induced disaster. The primary objective of this review is to distill valuable lessons than can help minimize the tragic consequences of earthquake-induced disasters. Methodology: This study comprises a meta-ethnography analysis drawing from various scientific manuscripts, online news sources, and Youtube channels. The manuscript scrutinizes five profoundly impactful earthquakes in Indonesia, specifically: Aceh earthquake, Padang earthquake, Yogyakarta earthquake, Palu earthquake, and Banten Earthquake Results: The proposed strategies outlined in this manuscript encompass the establishment of early warning systems for disaster preparedness, the implementation of urban planning for disaster-resilience, the identification of seismic hazard zone in densely populated areas, the enhancement of disaster education, and the promoting of earthquake-resistance construction practices. Applications/Originality/Value: The strategy for mitigating earthquake-induced disaster should follow the characteristics of disaster in the specific area. Understanding previous history of earthquake is prominent to determining the earthquake-induced disaster mitigation strategy.